Limited intrinsic postzygotic reproductive isolation despite chromosomal rearrangements between closely related sympatric species of small ermine moths (Lepidoptera: Yponomeutidae). (24th June 2019) - Hora, Katerina H; Marec, František; Roessingh, Peter; Menken, Steph B J
Abstract: In evolutionarily young species and sympatric host races of phytophagous insects, postzygotic incompatibility is often not yet fully developed, but reduced fitness of hybrids is thought to facilitate further divergence. However, empirical evidence supporting this hypothesis is limited. To assess the role of reduced hybrid fitness, we studied meiosis and fertility in hybrids of two closely related small ermine moths, Yponomeuta padella and Yponomeuta cagnagella, and determined the extent of intrinsic postzygotic reproductive isolation. We found extensive rearrangements between the karyotypes of the two species and irregularities in meiotic chromosome pairing in their hybrids. The fertility of reciprocal F1 and, surprisingly, also of backcrosses with both parental species was not significantly decreased compared with intraspecific offspring. The results indicate that intrinsic postzygotic reproductive isolation between these closely related species is limited. We conclude that the observed chromosomal rearrangements are probably not the result of an accumulation of postzygotic incompatibilities preventing hybridization. Alternative explanations, such as adaptation to new host plants, are discussed.